Variability of heart rate of elite athletes at deep breathing test - Sukhov, S. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Vegetative nervous system (VNS) plays important role in regulation of adaptation to intensive physical load. One of the informative noninvasive methods of study of VNS is analysis of variability of heart rate at deep breathing test (VHR at DBT). This test allows assessing the reaction to stimulation of the parasympathetic part of VNS. Goal of the study was to compare VHR at DBT of elite athletes and young male non-athletes. Methods: Twenty-five elite judoists (experimental group) and fifteen healthy young male non-athletes (control group) have been examined. VHR at DBT was conducted with use of hard- and software complex VNS-Spectrum. ECG was recorded in supine position during the performance of VHR at DBT (breath intake during 5 seconds and expiration for next 5 seconds, with total 6 breathing cycles a minute). Such breath rate causes a maximal stimulation of nervus vagus. Results: Respiratory coefficient (RC), that is, the ratio of maximum and minimum heart rates during the breathing cycle, was determined at analyzing the rhythmograms. Tachycardia at rest and reduction of this coefficient is symptomatic of deterioration of parasympathetic function. According to our findings, normally the RC should be above 1.35, and decrease of the coefficient down to 1.2 can be considered as the lower limit of normal. Athletes had the RC on level of 1.43±0.03 while in the control group it was 1.23±0.05 which evidences to the better functional status of athletes as compared to the control group. As a rule, at rest the athletes demonstrated prevalence of the parasympathetic part of VNS (background at rest vagotonia). In this case the equilibrium of different parts of VNS should be considered as an eutonia (balanced type). At long and draining exercises and decrease of fitness, the athletes demonstrate shift from the prevalence of parasympathetic part of VNS to the predominance of its sympathetic part. The notable maladjustment is accompanied with desynchronization of respiratory and vasomotor centers. Conclusion: DBT is an objective indicator of the status of parasympathetic part of vegetative nervous system and it allows getting the information on current functional status of athletes.